Safe Mobilization Practices of Patients on Impella 5.5® Ventricular Assist Devices: The Right Patient, the Right Timing, the Right Team - Katelyn Black; Stephanie Smith; Stephanie Koepke (Cardiopulmonary Physical Therapy Journal, 2026)
Purpose: The Johnson & Johnson MedTech Impella 5.5 ® is a temporary mechanical circulatory support (tMCS) device that supports cardiac output in the setting of cardiogenic shock. Older Impella ® models provide less cardiac output and limit mobility because of femoral insertion sites. It is widely accepted that early mobility is important in the ICU setting, but there is a lack of mobility-specific guidelines for patient selection or procedural interventions with the Impella 5.5 ® . This study describes a framework that was created to aid in patient selection for mobility, discusses procedures for those who are appropriate to mobilize, and provides single-center mobility data in patients with an Impella 5.5 ® temporary ventricular assist device. Methods: Retrospective chart review was performed on all 49 patients who had an Impella 5.5 ® device between April 2023 and September 2024. Variables retrieved from electronic medical records included mobility-related data (highest level of mobility, number of mobility events, device performance level (P-level) and pressors/inotropes at time of mobility), patient data (age, gender), and device data (placement location, duration of device, and concurrent/previous devices). Statistical analysis included percentages to understand data trends and frequency of mobility. Results: Twenty-four out of 49 (49%) of patients with an Impella 5.5 ® were deemed appropriate to mobilize based on the decision-making guideline, for a total of 62 mobility events. A vast majority (98%) of mobility events occurred with physical therapy or occupational therapy, with nursing accounting for the remaining 2%. There were no adverse events noted during mobility. Conclusions: The Johnson & Johnson MedTech Impella 5.5 ® provides up to 5.5 liters per minute of cardiac output, which allows the heart to recover from cardiogenic shock. When paired with interprofessional communication and training, a decision-making algorithm can aid in safe and effective mobilization of medically complex patients with an Impella 5.5 ® mechanical assist device.